Pathotyping of Escherichia coli Isolated from Inlets to Tehran Water Treatment Plants - Maryam Asghari; Abbas Akhavan Sepahi; Seyed Reza Hosseini Doost (آب و فاضلاب, 2016)
Water borne infections are of great importance for public health due to the role of water in the transmission of pathogens which cause gastrointestinal diseases. Traditional methods based on culture media commonly used for the identification of E. coli are not only time-consuming but fail to detect certain pathotypes of E. coli as well. To overcome these shortcomings, molecular methods were employed in the present study for the rapid and specific determination of E. coli pathotypes. For this purpose, 978 water samples were collected during the period from September 2012 to September 2013 and 106 E. coli strains were selected using multistep biochemical and molecular screening (tetraplex PCR) method. Virulogenes were determined by designing specific primers and developing efficient protocols. While it was shown that water has a great cabapility for transmiting pathogenic microorganisms, the results revealed that 10 strains contained the est, elt, and eaeA genes; five contained the bfpA gene; four contained the pCVD and ipaH genes; three contained the VT1 and VT2 genes; and finally one starin contained the cnf1 and cnf2 genes. It was also found that molecular methods based on our newly designed primers are sensitive, specific, and rapid protocols for pathotyping of Escherichia coli.